(3QSGdI aj GdefWbs - (3GHf edhcI , eMeO Hf UGdM Hf eLOj,J (B1276 (3g` s
(3ChdgG (B:s
(3hHYO aGYde jHfi aJM Gddg HUjQJc hWgQ SQjQJc s
(3BNQgG (B:s
(3GdQHY GdKGfi hGdQHY GdKGdK hGdLedI SHYI eY KGdK GdKGfi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B88s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3efWb JjehQ (B162) s
Keywords: (3GdadSaI hGdefWbs